Register in The Good Doctor Movie - Muhammad Fadli Hasan; Ansor Putra; Rasiah Rasiah (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study aims to describe the types and functions of register used in The Good Doctor (season 5 episode 18). This research is qualitative and descriptive with The Good Doctor movie as the data source. The data were collected by watching, annotating, and coding. Analysis by presenting, describing, analyzing, and concluding the data. This research found there are 60 utterances of type of registers used in the movie such as Frozen, Formal, Consultative, Casual, and Intimate. Then, the researcher also found that there are sixty-six data on the function of the register including Emotive (13), Directive (21), Referential (26), Peotic (1), and Phatic (5). In this movie, the researcher found all types of registers used by characters. For the function of the register, the researcher only found five of six functions in the movie. The most used type of register is the casual register with twenty-eight data and referential is most used by characters in the movie with twenty-six data. The use of a casual register can reflect a more relaxed speaking style, not overly formal, and closer to everyday conversation. The metalinguistic function was not found because there are no situations where characters have a conversation that refers to the metalinguistic function in the movie.